Regularização fundiária e conflitos fundiários no Norte Araguaia em Mato Grosso - Lino, Kennia Dias (2014)
: This study 's purpose is to secure tenure and land conflicts in Amazonia from a legal perspective. The discussion of the present work is guided by the question of understanding the Agrarian Law on the regularization performed in the Amazon made by the federal government from the 1960s to the year 2012. For this analysis, this issue will be confronted with agrarian conflicts in a specific area of the Amazon: the Araguaia Northern Mato Grosso. On theoretical grounds the studies of Charles Frederick Tide are used to analyze the concept of property possession and present policies of regularization and José de Souza Martins for understanding the relationship man/weather/land border situation, as is the case North Araguaia Mato Grosso. The methodology of this study is to understand the legal phenomenon, land use regulation in a broader social environment that is the agrarian conflict, by means of literature with analysis of legislation and qualitative data. Thus, initially, it approaches the institute of public lands, the settlement pattern of these and their importance within the regularization. Furthermore, we present an analysis of the laws of regularization in the Amazon permeating this subject by land problem in this region by the military dictatorship government of Fernando Henrique Cardoso. Finally, it examines the regularization relating it to the laws of the Lula government and agrarian conflicts.